The interrelationship of civil society organizations and participatory budget in Carchi province - Mora Coral, Roger Fernando; Rosero Coral, Daira Yimabel; Valverde Obando, Adrián Alexander (SATHIRI, 2020)
The Participatory Budget is one of the 7 mechanisms of citizen participation armed with the 2008 Constitution, which promotes the direct and permanent intervention of civil society and in general citizens, both in planning and public management. This article explains the interrelationship between Civil Society Organizations (CSOs) and the Participatory Budget (PB) in Carchi Province during the period 2015-2017. As a methodological part, the type of descriptive and phenomenological research are used, addressing reality from an individual’s internal frame of reference and knowing experiences of the participants. The presentation of results shows two factors limiting an effective interrelationship between civil society organizations and participatory budget, the first, the political unwillingness in processes of dissemination and socialization, and the second, the lack of social awareness of citizens for the matters of public interest inherent in their territory.